Pengaruh Pemasaran Celebrity Endorsment pada Media Sosial Instagram Terhadap Minat Beli pada Produk Pakaian Kaum Wanita Generasi Z Dikota Karawang - Desi Jaelani; Dessy Herdiana; Abdul Yusuf (Masyarakat Ekonomi Syariah Bogor, 2024)
A Celebrity Endorsement figure not only has an attractive face and appearance, but must also have aspects commonly known as VISCAP which consist of popularity (Visibility), expertise (Credibility), attractiveness (Attractiveness), strength (Power) and ability. influence consumer buying interest. (Royan, 2005). The online shop business is currently growing quite rapidly, to meet the needs of many online shops which continue to grow and compete to win the market so they can win the hearts of their consumers. This type of research uses quantitative research methods, which according to (Sugiyono, 2014: 8) are said to be quantitative methods because quantitative research can be interpreted as a research method that is based on the philosophy of positivism. Used to research certain populations or samples, data collection using research instruments, quantitative/statistical data analysis, with the aim of testing predetermined hypotheses. Based on the research results, it can be concluded that there is a positive and significant influence between Instagram celebrity endorsement marketing on the interest in purchasing clothing products among Generation Z women in Karawang City. This is proven by the coefficient of determination (R2) which is quite high, namely 70.5%. while the remaining 29.5%. This shows that 70.5% of the variation in interest in buying clothing products among Generation Z women in Karawang City can be explained by the Instagram celebrity endorsement variable.